Spatial distribution of Plasmodium knowlesi cases and their vectors in Johor, Malaysia : in light of human malaria elimination - Sandthya, Pramasivan; Romano, Ngui; Nantha Kumar, Jeyaprakasam; Jonathan Wee, Kent Liew; Van, Lun Low; Norzihan, Mohamed Hassan; Wan Yusoff, Wan Sulaiman; Ropiah, Jaraee; Roslinda, Abdul Rahman; Jenarun, Jelip; Indra, Vythilingam (BioMed Central Ltd., 2021)
Background: Plasmodium knowlesi, a simian malaria parasite infection, increases as Plasmodium falciparum and Plasmodium vivax infections decrease in Johor, Malaysia. Therefore, this study aimed to identify the distribution of vectors involved in knowlesi malaria transmission in Johor. This fnding is vital in estimating hotspot areas for targeted control strategies. Methods: Anopheles mosquitoes were collected from the location where P. knowlesi cases were reported. Cases of knowlesi malaria from 2011 to 2019 in Johor were analyzed. Internal transcribed spacers 2 (ITS2) and cytochrome c oxidase subunit I (COI) genes were used to identify the Leucosphyrus Group of Anopheles mosquitoes. In addition, spatial analysis was carried out on the knowlesi cases and vectors in Johor. Results: One hundred and eighty-nine cases of P. knowlesi were reported in Johor over 10 years. Young adults between the ages of 20–39 years comprised 65% of the cases. Most infected individuals were involved in agriculture and army-related occupations (22% and 32%, respectively). Four hundred and eighteen Leucosphyrus Group Anopheles mosquitoes were captured during the study. Anopheles introlatus was the predominant species, followed by Anopheles latens. Spatial analysis by Kriging interpolation found that hotspot regions of P. knowlesi overlapped or were close to the areas where An. introlatus and An. latens were found. A signifcantly high number of vectors and P. knowlesi cases were found near the road within 0–5 km. Conclusions: This study describes the distribution of P. knowlesi cases and Anopheles species in malaria-endemic transmission areas in Johor. Geospatial analysis is a valuable tool for studying the relationship between vectors and P.knowlesi cases. This study further supports that the Leucosphyrus Group of mosquitoes might be involved in transmitting knowlesi malaria cases in Johor. These fndings may provide initial evidence to prioritize diseases and vector. surveillance